Application of transcranial color-coded sonography in severe brain injury - Turek, Radovan; Linzer, Petr; Filip, Michal; Sámal, Filip; Jurek, Patrik (Acta neurochirurgica. Supplementum, 2013)
Transcranial color-coded sonography (TCCS) monitoring of severe brain injury patients may reveal various pathological hemodynamic changes. According to changes in flow velocities in basal brain arteries, the presence of brain hyperemia, vasospasms, and oligemia can be detected. The study included a group of 20 patients with severe brain injury. TCCS measured flow velocities and ICP values were monitored on a daily basis in the course of a week after injury. In nearly 50 % of patients significant hemodynamic changes occurred. The most frequent pathological finding was hyperemia (31.8 %), followed by vasospasm (10.9 %) and oligemia (9.1 %). In 42.7 % of patients increased flow velocities were registered and only 9.1 % of records were within the normal range of values. The most substantial elevation in time-averaged mean velocity occurred from the second to the sixth day after injury. In a subgroup of patients with raised intracranial pressure 41.6 % of flow velocity (FV) measuring met the TCCS criteria for hyperemia compared with 26 % in a subgroup of patients without intracranial pressure (ICP) elevation. The study showed that hemodynamic changes after severe brain injury are relatively common findings and that TCCS is a useful bed-side tool for the monitoring of intracranial hemodynamic changes.
Keywords: Cerebrovascular Circulation; Brain Injuries; Female; ženské pohlaví; mozkový krevní oběh; klinické kódování; Time Factors; časové faktory; lidé; poranění mozku; následné studie; rychlost toku krve; Blood Flow Velocity; ultrasonografie dopplerovská transkraniální; Clinical Coding; Intracranial Pressure; intrakraniální tlak; Follow-Up Studies; Male; Vasospasm, Intracranial; Ultrasonography, Doppler, Transcranial; mužské pohlaví; intrakraniální vazospazmus; Humans